2018
DOI: 10.1093/molbev/msy170
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Map of Genetic Variation in the World’s Largest Ethnic Group—Han Chinese

Abstract: As are most non-European populations, the Han Chinese are relatively understudied in population and medical genetics studies. From low-coverage whole-genome sequencing of 11,670 Han Chinese women we present a catalog of 25,057,223 variants, including 548,401 novel variants that are seen at least 10 times in our data set. Individuals from this data set came from 24 out of 33 administrative divisions across China (including 19 provinces, 4 municipalities, and 1 autonomous region), thus allowing us to study popul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 89 publications
8
60
0
Order By: Relevance
“…Our results showed that Han Chinese populations – long believed to the decedents of Yanhuang Emperors who shared similar cultural artifacts and underwent several southward migrations as well as an admixture with southern indigenous minorities – presented a population stratification (Wen et al, 2004). Significant genetic difference between North-China Han and South-China Han was identified, which is consistent with the earlier research findings via maternal mitochondrial, paternal Y-chromosomal and autosomal genetic materials (Chen et al, 2009; Xu et al, 2009; Nothnagel et al, 2017; Chiang et al, 2018). This North-to-South cline is dependably supported by our heat map, MDS, N-J phylogenetic relationship reconstruction and PCA analyses, as well as illustrated by the low pairwise Reynolds’ genetic distance within South Han Chinese populations and Northern Han Chinese populations and larger genetic distance between them.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that Han Chinese populations – long believed to the decedents of Yanhuang Emperors who shared similar cultural artifacts and underwent several southward migrations as well as an admixture with southern indigenous minorities – presented a population stratification (Wen et al, 2004). Significant genetic difference between North-China Han and South-China Han was identified, which is consistent with the earlier research findings via maternal mitochondrial, paternal Y-chromosomal and autosomal genetic materials (Chen et al, 2009; Xu et al, 2009; Nothnagel et al, 2017; Chiang et al, 2018). This North-to-South cline is dependably supported by our heat map, MDS, N-J phylogenetic relationship reconstruction and PCA analyses, as well as illustrated by the low pairwise Reynolds’ genetic distance within South Han Chinese populations and Northern Han Chinese populations and larger genetic distance between them.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in the Trans-Omics for Precision Medicine (TOPMed) Program, only $10% of its 145,000 samples are Asians (Taliun et al, 2019). In Asia, most published WGS studies have small sample sizes (Bai et al, 2018;Wong et al, 2013Wong et al, , 2014, except for two recent studies of Chinese by 1.73 and 0.13 WGS, respectively (Chiang et al, 2018;Liu et al, 2018). Extremely shallow sequencing, however, has low sensitivity to detect rare variants and, thus, limited power for evolutionary inferences and other population genetics analyses (Li et al, 2011;Han et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Next‐generation sequencing data have become more prevalent in genetic studies as the cost of whole‐genome sequencing has decreased (Chiang et al., ; Francioli et al., ; Liu et al., ; UK10K Consortium, ). This has also led to an increased number of large‐scale sequencing studies of samples with diverse ancestries (1000 Genomes Project Consortium et al., , ).…”
Section: Introductionmentioning
confidence: 99%